2020
DOI: 10.3390/particles3030037
|View full text |Cite
|
Sign up to set email alerts
|

Gauge Dependence of the Gauge Boson Projector

Abstract: The propagator of a gauge boson, like the massless photon or the massive vector bosons W± and Z of the electroweak theory, can be derived in two different ways, namely via Green’s functions (semi-classical approach) or via the vacuum expectation value of the time-ordered product of the field operators (field theoretical approach). Comparing the semi-classical with the field theoretical approach, the central tensorial object can be defined as the gauge boson projector, directly related to the completeness relat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…To maintain the gauge invariance, Ref. [29] suggests that if the boson V is SU (2) dark Z, one shall compute the tree-level amplitude squared by using unitary gauge [30,31]. Regardless of the gauge choice, for the vector interaction with C a N = 0, we find that its amplitude squared is unaffected.…”
Section: Effective Inelastic Dm Interactionsmentioning
confidence: 82%
“…To maintain the gauge invariance, Ref. [29] suggests that if the boson V is SU (2) dark Z, one shall compute the tree-level amplitude squared by using unitary gauge [30,31]. Regardless of the gauge choice, for the vector interaction with C a N = 0, we find that its amplitude squared is unaffected.…”
Section: Effective Inelastic Dm Interactionsmentioning
confidence: 82%
“…To maintain gauge invariance, ref. [30] indicates that if the boson V is SU(2) dark Z, the tree-level amplitude squared must be computed with a unitary gauge [31,32], which will be considered in this study for both the vector and axial-vector interactions.…”
Section: Figurementioning
confidence: 99%
“…In a recent study in Ref. [74], it was shown that the unitary gauge is the default gauge for massive gauge bosons.…”
Section: Cp Asymmetry Ofmentioning
confidence: 99%